Estudio de la infraestructura tecnológica de soporte al comercio electrónico en los productores agrícolas de la Parroquia San Juan. - Avilés Amador, Mercedes Samantha (2023)
The technological infrastructure to support electronic commerce is of great importance for agricultural producers in the parish of San Juan because it allows them to expand their clientele and increase efficiency in the management of orders, payments and deliveries. With e-commerce platforms, producers can reach a larger and more diverse audience, allowing them to enter new markets both nationally and internationally. Furthermore, technology can improve communication with customers so that they can better understand their needs and deliver products and services that meet their expectations. It can also improve product traceability, which is effective for consumers looking for healthier and safer food. In general, the technological infrastructure that supports electronic commerce can improve the competitiveness and profitability of the agricultural producers of the San Juan Parish, contributing to the sustainable development of the agricultural sector.